The evaluation of volunteer program for cataract surgery in Phatthalung hospital for fiscal year 2020 - Ngaorungsee, Aoraporn (Region 11 Medical Journal, 2022)
Objective: To analyze context, input factors, processes, and outcomes of volunteer program for cataract surgery in Phatthalung hospital 2020. Design: Evaluation research using the CIPP model. Methods: The purposive sampling included 20 medical professionals and 181 patients in the campaign. The data was gathered by questionnaires and was analyzed using frequencies, percentages, standard deviations, and content analysis. Results: The level of perceived appropriateness for context perspective was high (ˉx = 4.30, S.D. = 0.64). The most appropriate aspect was the objectives were aligned with Phatthalung hospital’s policies (ˉx = 4.75, S.D. = 0.43). The campaign was helpful for the patients who needed cataract surgery (ˉx =4.55, S.D. = 0.67). The input factors aspect was perceived to be highly appropriated (ˉx = 3.65, S.D. = 0.69). The work processes aspect was also found to be highly appropriated (ˉx = 3.88, S.D. = 0.74). The outcomes of the campaign were perceived as highly appropriated (ˉx = 3.73, S.D. = 0.79). Moreover, the patients would highly appreciate if this campaign continued (ˉx =4.50, S.D. = 0.50). Conclusion: According to the results, the campaign is highly satisfying, input factors, processes, and outcomes of volunteer program for cataract surgery in Phatthalung hospital